The Assessment of Acupuncture and Exercise Therapy in Patients with Carpal Tunnel Syndrome: Randomized Clinical Trial - Salehi, Shahin; Hessami, Omid; Rashed, Amir; Hassabi, Mohammad; PourSaeid Esfehani, Mehrshad; Abedi Yakta, Amirhosein; Mahdavi Mohtasham, Hamid; Khosravi, Shahrzad; Mohaghegh, Shahram; Sohrabi, Mohammad Reza (Novelty in Biomedicine, 2019)
Background: The efficacy of acupuncture and exercise therapy in the treatment of carpal tunnel syndrome (CTS) has been investigated in limited studies with controversial results. The purpose of this study was to compare the short-term efficacy of acupuncture and exercise therapy in patients with mild to moderate CTS. Materials and Methods: This study was a randomized controlled clinical trial study conducted on 60 patients (55 women) with mild to moderate CTS referring to Imam Hossein Hospital in Tehran in 2017. The patients were randomly divided in to 3 equal groups; groupa1: only night splint was used for 6 weeks (control), group2: splint with tendon and nerve gliding exercises (2 times a day for 6 weeks) were applied, group3: splint and electroacupuncture was performed for 12 sessions (2 sessions/week). The score on the Boston Carpal Tunnel Questionnaire (BCTQ) for Functional Status and Symptom Severity (BCTQ FUNCT and SYMPT) and visual analog scale (VAS) score were evaluated at baseline and after the treatment. Results: At the final follow up, significant improvements in all parameters of quality of life and VAS were found in third groups (p<0.05). Acupuncture affected the score on the BCTQ FUNCT and SYMPT, the VAS score more than exercise therapy. In addition, the efficacy of splint alone was less than intervention groups in all parameters. Conclusion: Acupuncture with splint has a high effect on reducing pain and improving the quality of life in patients with mild to moderate CTS and could be adopted in the management of these patients.